Equation Project
By James Roh

The Equation
18x + 6 - 3x = 7(x + 21) + x - 15

Step 1
First, you have to simplify
18x - 3x by combining like
terms and multiply 7(x+21)
using the distributive
property. After that you
need to combine like terms
again by adding x to 7x
and subtracting 15 from
147.
18x + 6 - 3x = 7(x + 21) + x - 15
15x + 6 = 7x + 147 + x - 15
15x + 6 = 8x + 132

Step 2
Next you will need to
eliminate the
variables on one
side by subtracting
the
smallest
variable in the
equation which is 8x.
15x + 6 = 8x + 132
-8x
-8x
7x + 6
= 132

Step 3
Now you have to subtract
the constants, which is 6
from both sides because
you want to have 7x
alone.
7x + 6 = 132
- 6
- 6
7x = 126

Step 4
For the final step, you
will need to divide both
sides by the coefficient
of 7x to find what x
equals.
7x
= 128
7
=
7
x
=
18

Check
For the check, you have
to substitute x and use the
order of operations.
18(18) + 6 - 3(18) = 7[(18) + 21] + 18 - 15
324 + 6 - 54 = 7(39) + 18 - 15
330 - 54 =
273 + 3
276 =
276

THE END